ANALISA HUKUM KEBERADAAN KUASA MUTLAK DALAM AKTA PERJANJIAN PENGIKATAN JUAL BELI ATAS TANAH - Clarissha, Vindria Shafa; Wisnaeni, Fifiana (Legal Standing : Jurnal Ilmu Hukum, 2023)
Since the instruction of the Minister of Home Affairs No. 14 of 1982 regarding the prohibition of giving absolute power of attorney in line with the transfer of land rights which took effect on March 6, 1982 and PP No. 24 of 1997 concerning land registration came into force on 4 July 1997, the use of absolute power of attorney is no longer permitted. However, in practice absolute power in land purchase agreements is still often used. The research to be carried out is a type of normative legal research through a review of literature and also legal materials, for example research on legal principles and rules and legal rules. The results of the study show that not any use of absolute power related to the sale and purchase of land is not permitted as long as it is not intended for the transfer of rights to land. The use of absolute power of attorney related to the Land Sale and Purchase Binding Agreement made before a notary is only aimed at protecting and guaranteeing legal certainty for the parties involved, especially the buyer that the sale and purchase process can later take place according to what was agreed when the terms of the sale and purchase have been fulfilled. regarding the use of absolute power of attorney in binding agreements for sale and purchase of land is legal and not a violation of laws and regulations. Another thing is that the legal impact arising from this use is absolute and is still recognized and continues to be enforced and binding for related parties.